National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 7 already been described. For the general financing of their hospital services, however, they will look to the Exchequer and they will be given as much financial freedom — by a system of block annual budgets or otherwise — for local initiative and variety of enterprise as general principles of exchequer responsibility make possible. Teaching hospitals 25. Special arrangements are provided for teaching hospitals — that is, hospitals or groups of related hospitals which are designated by the Minister as providing the facilities for undegraduate [undergraduate] or post-graduate clinical teaching. These will enable any hospital or group of hospitals to attain "teaching" status whether it is already a teaching hospital at the outset of the scheme or not. 26. The general system of Regional Boards and Management Committees will not cover the teaching hospitals. The Minister is to constitute for each such hospital or group of hospitals its own separate Board of Governors, including members nominated by the university, the Regional Board for the area, and the senior staff of the hospital itself and members appointed after consultation with the major local authorities and other organisations concerned, including the previous governing bodies. The Board of Governors of a teaching hospital will be responsible generally for administering their hospital on the Minister's behalf. 27. The financial arrangements in regard to existing voluntary endowments of the teaching hospitals have already been described. For the general financing of their services they will look to the exchequer and again the general object will be to assure them all the financial freedom and autonomy of management which the general conception of a nationally reorganised and nationally financed service makes possible. In this case, in addition, it is intended to keep in the forefront of any arrangements the special position of these hospitals as the centres of clinical teaching and technical experiment and innovation. 28. The fact that special administrative and financial arrangements may be made for teaching hospitals does not mean, however, that these hospitals are not to form an integral part of the hospital service as a whole. They will be joined with the Minister and the Regional Boards in the general planning and arrangement of the hospital services of each Region, and the Regional Boards will be represented on their Boards of Governors. Medical and dental schools 29. Medical and dental schools are not to be transferred to the Minister or to the Board of Governors of the teaching hospital with which they are associated. No property which is held for the purposes of these schools is to be transferred. The schools will continue to be owned and administered, in London, by their own governing bodies, and elsewhere by the governing bodies of the universities of which they form part; and the Bill provides for the transfer of any existing hospital property held for school purposes to these governing bodies. 30. The Bill contains also a special provision relating to medical and dental schools, based on recommendations of the Interdepartmental Committee on Medical Schools (the Goodenough Committee). Any medical or dental school of London University which is not yet a body corporate is required to take steps within six months of the passing of the Bill to become incorporated. 292/847/4/115